2021
DOI: 10.3389/fonc.2021.629207
|View full text |Cite
|
Sign up to set email alerts
|

A Pragmatic Non-Randomized Trial of Prehabilitation Prior to Cancer Surgery: Study Protocol and COVID-19-Related Adaptations

Abstract: BackgroundExperimental data highlight the potential benefits and health system cost savings related to surgical prehabilitation; however, adequately powered randomized controlled trial (RCT) data remain nascent. Emerging prehabilitation services may be informed by early RCT data but can be limited in informing real-world program development. Pragmatic trials emphasize external validity and generalizability to understand and advise intervention development and implementation in clinical settings. This paper pre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 79 publications
0
9
0
Order By: Relevance
“…The benefits of multimodal prehabilitation continue to be explored via large trials [68], and programmes are increasingly being incorporated into standard care [69]. As more studies are conducted, it is vital to examine the target populations and the outcomes of these programmes.…”
Section: Discussionmentioning
confidence: 99%
“…The benefits of multimodal prehabilitation continue to be explored via large trials [68], and programmes are increasingly being incorporated into standard care [69]. As more studies are conducted, it is vital to examine the target populations and the outcomes of these programmes.…”
Section: Discussionmentioning
confidence: 99%
“…Our study found that utilizing trained research assessment staff for anthropometric and physical performance testing, along with the Zoom application, camera and internet connection, made these assessments feasible and safe. This is an important contribution to the literature and presents a different approach from other researchers who adapted in person research during COVID-19 in cancer survivors and other populations [2,[5][6][7]. In one study, investigators chose to forgo collecting objective outcomes (e.g., body composition, 6-min walk test) in individuals with cancer and focused only on outcomes that they could collect remotely (e.g., questionnaire data and data from electronic medical records) [7].…”
Section: Discussionmentioning
confidence: 99%
“…This is an important contribution to the literature and presents a different approach from other researchers who adapted in person research during COVID-19 in cancer survivors and other populations [2,[5][6][7]. In one study, investigators chose to forgo collecting objective outcomes (e.g., body composition, 6-min walk test) in individuals with cancer and focused only on outcomes that they could collect remotely (e.g., questionnaire data and data from electronic medical records) [7]. Importantly, that study was conducted among cancer patients prior to their cancer surgery: investigators may have deemed that it was safest to omit in-person functional assessments because participants may have been most vulnerable at this point of their cancer journey.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…11 Hence, in recent years, prehabilitation evidence has grown in patients who are frail, higher risk and/or vulnerable to perioperative complications who are likely to benefit most from prehabilitation. 12 With a paucity of evidence conducted on the higher risk pre-frail and frail population planned for elective major abdominal surgery, there is a need to investigate the impact of a multimodal prehabilitation supervised program in mitigating postoperative functional decline when compared to standard care.…”
Section: Introductionmentioning
confidence: 99%